A Descriptive Study to Assess the Knowledge Regarding Contraceptive Method Among the Married Couples of Chaubepur, Kanpur - Bhushan, Monika; Khan, Nadeem; Singh, Yogendra; Patel, Preeti; Kumari, Priyanka (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Client-centric quality of care (QoC) in family planning (FP) services are imperative for contraceptive method adoption and continuation. Less is known about the choice of contraceptive method in India beyond responses to the three common questions regarding method information, asked in demographic and health surveys. This study argues for appropriate measurement of method choice and assesses its levels and correlates in rural India. A quantitative research approach and descriptive research design was used the research setting was selected areas Chaubepur, Kanpur (Chaubepur, dist.-Kanpur Nagar, U.P) Total 60 people were selected with the purposive sampling technique. Written consent was taken from the people who were selected as sample. Self- structured knowledge questionnaire containing 30 questions and checklist containing 10 questions was used to evaluate the knowledge and practice of people regarding contraceptive method. Result depicted the mean knowledge and practice score of people was 14.67 and mean of practice was 4.7. This mean score was statistically significant at p
Keywords: people; knowledge; practice